Analisis Pembiasaan Budaya Positif Guna Penguatan Pendidikan Karakter di SMK Negeri 1 Mojokerto - Dinda Masyita Putri Kurnia Dimmaja; Amalia Rohmatin Nazili; Ragil Sri Wahyuningsih; Rafika Dini; Sofi Ullanuha Cahyani; Reisya Diva Maharani Putri; Vita Cahya Puspita; Amy Krisdiana; Sucoko Sucoko (Jurnal Cakrawala Pendidikan dan Biologi, 2024)
This research aims to determine the impact of habituating positive culture at SMK Negeri 1 Mojokerto and its influence on strengthening students' character education. Education plays an important role in daily life and has a significant impact on individual growth and development. The goals of education include developing good character and reinforcing positive values among students. Through the implementation of a positive culture, it is expected that students can demonstrate disciplined behavior without coercion, increase their interest in learning, and achieve better academic performance. A qualitative research method was used by distributing questionnaires to 30 students of SMK Negeri 1 Mojokerto. The results indicate that the habituation of a positive culture has a significant effect on strengthening students' character education, creating self-discipline, and fostering good morals within the school environment. Therefore, the importance of consistently implementing a positive culture can enhance students' character education and discipline.